(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
By studying both species the results showed that the average weights of adult birds were 1445 gm in ducks. the average rate of tongue’s weight was 8.87 gm, and a relative weight of 0.61 gm, while the average weights in geese were 2374 gm, 11.28 gm, and 0.47 gm, respectively. The dorsal surface of the apex of the tongue of ducks was spoon-shaped, while the apex of the tongue of geese was round. but the ventral surface was triangular with a white plate termed the nail of the tongue in both species. The caudal part of the duck tongue makes the tongue comb which is placed in front of the lingual elevation, whereas the caudal part of the goose tongue forms the median furrow which is located at the front border of the lingual elevation. The margins of the tongue of both animals include large and small conical mechanical papillae, in addition to filiform papillae. A significant difference has been noted in the thickness of the apex and the root of the tongue between the two birds. Also, there was a significant difference in the width of the lingual elevation and root between the two birds.